Sitka: a collaboration between type design and science - Larson, Kevin; Carter, Matthew (Digital Fonts and Reading, 2016)
We recognize words by first recognizing individual letters, then using the letters to build a word [Larson, 2004; Rayner et.al, 2012]. Words become more readable by making each of the individual letters more recognizable. This chapter is about the development process for a new typeface named Sitka. During the typeface’s development, we tested how well people could read each of the letters in the typeface, and used the test results to inform design decisions. While the test results needed to be applied conscientiously, we discovered that typeface design could be successfully integrated with scientific legibility testing. Interview with Matthew Carter